Parental species and hybrid descendants of Bacillus (Insecta Phasmatodea) show different patterns of highly amplified, colocalized ribosomal and telomeric sequences. Issue 1 (1st January 2020) - Scali, V.; Deidda, F.; Coluccia, E.; Cannas, R.; Melis, R.; Salvadori, S.
Abstract: We investigated by dual-color fluorescence in situ hybridization (FISH) with 28S ribosomal and (TTAGG)n telomeric probes all species of the circum-Mediterranean genus Bacillus encompassing bisexual and parthenogenetic taxa, namely the three parental species ( B. grandii, B. atticus, B. rossius ) and the two derived hybrids ( B. whitei, B. lynceorum ). Specimens were collected in Italian mainland, Sardinia and Sicily. In all species the presence of colocalized, highly amplified ribosomal and telomeric sequences was demonstrated by the double labelling of the cytological satellites. These satellites varied in size, number and location both among and within species. In B. grandii and B. atticus a maximum of two FISH-labeled locations were observed, whereas in B. rossius and in the two hybrids up to 11 different positions were recorded. Moreover, our investigations showed a significant occurrence of chromosome breakages and rearrangements. The overall meaning of the ribosomal and telomeric sequence colocalization as well as the Nucleolar Organizer Region mobility and activity are discussed in both the ancestors and their hybrid descendants. It is noteworthy that the same trait has been shown in seven additional phasmid species belonging to distantly related genera. This trait could be a shared ancestral character in phasmids.